Solid electrolytic capacitor and hybrid electrolyte capacitor
Patent Information
- Application Number
- JP2024153865
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-06
- Filing Date
- 2024-09-06
- Publication Date
- 2025-03-26
Smart Images

Figure 2025041553000001_ABST
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE Embodiments of the present invention relate to electrolytic capacitors, and in particular to the composition of the electrolyte therein. [Background technology]
[0002] Electrolytic capacitors are usually made by oxidizing the surface of a metal to form a porous dielectric, and then filling this porous structure with a liquid or solid conductive material to form the cathode and anode. A commonly used aluminum capacitor is made in a wound or stacked form, connected to the outside by other tabs, and packaged. This results in an electrolytic capacitor. Summary of the Invention [Problem to be solved by the invention]
[0003] Existing electrolytic capacitors have a relatively high low-temperature capacitance fade rate and low-temperature ESR increase rate at low temperatures, so there is a strong demand for a new electrolyte composition to solve these problems. [Means for solving the problem]
[0004] An embodiment of the present invention provides a solid electrolytic capacitor, which includes an anode foil having a dielectric oxide film thereon, a cathode foil, a separator located between the anode foil and the cathode foil, and a solid electrolyte formed on the surface of the dielectric oxide film on the anode foil, the solid electrolyte including a conductive polymer and a zwitterionic compound, wherein the chemical structure of the zwitterionic compound is as follows:
[0005] [ka]
[0006] In the formula, R 1 is C 1-6 R is a straight or branched alkyl group. 2 , R 3 , and R 4 are each independently H or C 1-6is a straight or branched alkyl group of the formula 1-12 is a straight-chain or branched-chain alkylene group.
[0007] In some embodiments, the zwitterionic compound comprises between 1 wt % and 50 wt % of the solid electrolyte.
[0008] In some embodiments, the conductive polymer includes poly(3,4-ethylenedioxythiophene:polystyrenesulfonate) (PEDOT:PSS), polythiophene, poly(p-phenylene sulfide), polycarbazole, polyindole, polyaniline, polypyrrole, poly(fluorene), polyphenylene, polypyrene, polyazulene, polynaphthalene, poly(acetylene), or poly(p-phenylene vinylene).
[0009] An embodiment of the present invention provides a hybrid electrolytic capacitor, which includes an anode foil having a dielectric oxide film thereon, a cathode foil, a separator located between the anode foil and the cathode foil, a solid electrolyte formed on the surface of the dielectric oxide film on the anode foil and including a conductive polymer, and a liquid electrolyte filled in the space between the anode foil, the cathode foil, and the separator and including a solvent having a boiling point higher than 150° C., wherein the solid electrolyte, the liquid electrolyte, or both include a zwitterionic compound, the chemical structure of which is as follows:
[0010] [ka]
[0011] In the formula, R 1 is C 1-6R is a straight or branched alkyl group. 2 , R 3 , and R 4 are each independently H or C 1-6 is a straight or branched alkyl group of the formula 1-12 is a straight-chain or branched-chain alkylene group.
[0012] In some embodiments, when the solid electrolyte comprises a zwitterionic compound, the zwitterionic compound comprises between 1 wt % and 50 wt % of the solid electrolyte.
[0013] In some embodiments, when the liquid electrolyte includes a zwitterionic compound, the zwitterionic compound comprises between 1 wt % and 50 wt % of the liquid electrolyte.
[0014] In some embodiments, when the solid electrolyte and the liquid electrolyte include a zwitterionic compound, the chemical structure of the zwitterionic compound in the solid electrolyte and the chemical structure of the zwitterionic compound in the liquid electrolyte are the same.
[0015] In some embodiments, when the solid electrolyte and the liquid electrolyte include a zwitterionic compound, the chemical structure of the zwitterionic compound in the solid electrolyte is different from the chemical structure of the zwitterionic compound in the liquid electrolyte.
[0016] In some embodiments, the solvent with a boiling point greater than 150° C. includes propylene glycol, glycerol, gamma-butyrolactone, gamma-valerolactone, N-methylpyrrolidone, dimethylsulfoxide, or sulfolane.
[0017] In some embodiments, the liquid electrolyte further comprises a liquid polymer.
[0018] In some embodiments, the liquid polymer includes a polyalkylene glycol. [Brief description of the drawings]
[0019] [Figure 1]FIG. 2 is an explanatory diagram of a wound blank electrode body in one embodiment of the present invention. [Figure 2A] FIG. 2 is an explanatory diagram of an electrode body and a solid electrolyte according to one embodiment of the present invention. [Figure 2B] FIG. 2 is an explanatory diagram of an electrode assembly and a hybrid electrolyte in one embodiment of the present invention. [Diagram 3] FIG. 2 is an explanatory diagram of an electrolytic capacitor according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] In one embodiment of the present invention, a capacitor is made using the wound blank electrode body. As shown in FIG. 1, the anode foil 101 and the cathode foil 103 included in the wound blank electrode body 100 are metal foils, and the anode foil 101 further has a dielectric oxide film 201 thereon, for example, a porous metal oxide. A separator 102 is interposed between the anode foil 101 and the cathode foil 103. The anode foil 101 and the cathode foil 103 may each be beryllium, magnesium, aluminum, germanium, tin, antimony, bismuth, titanium, zirconium, hafnium, vanadium, niobium, tantalum, tungsten, or an alloy thereof. The dielectric oxide film 201, for example, a porous metal oxide, may be a porous oxide corresponding to the metal of the anode foil 101. For example, the anode foil 101 may be an aluminum foil, and the dielectric oxide film 201 may be a porous aluminum oxide. The separator 102 may be cellulose, polyethylene terephthalate, polybutylene terephthalate, polyethylene, polypropylene, polyvinylidene fluoride, other suitable polymers, blends thereof, or multi-layers thereof. The anode foil 101, cathode foil 103, and separator 102 are wound into a roll, and the anode lead 104 and cathode lead 105 are connected to the anode foil 101 and cathode foil 103, respectively, to form the wound blank electrode assembly 100.
[0021] As shown in Fig. 2A, a solid electrolyte 202 can be formed on the surface of the dielectric oxide film 201 on the anode foil 101 in the wound blank electrode body 100. The method of forming the solid electrolyte 202 may be to immerse the wound blank electrode body 100 in a dispersion liquid containing a solid electrolyte, and repeatedly draw a vacuum multiple times to cause the dispersion liquid containing the solid electrolyte to be adsorbed on the surface of the dielectric oxide film 201 on the anode foil 101 of the wound blank electrode body 100, and then dry it. By repeating the steps of adsorption and drying, the solid electrolyte 202 is formed on the surface of the dielectric oxide film 201 on the anode foil 101.
[0022] 3, the wound blank electrode assembly 100 with solid electrolyte 202 is placed into a case 301. A cap 302 is fitted onto the case 301, and then a sealant 303 seals the gaps between the case 301, cap 302, anode lead 104, and cathode lead 105 to form a seal 300, i.e., a solid electrolytic capacitor (only solid electrolyte 202, no liquid electrolyte).
[0023] In addition, the solid electrolyte 202 is formed on the surface of the dielectric oxide film 201 on the anode foil 101 in the wound blank electrode body 100. The method of formation is as described above, and will not be repeated here. Next, the wound blank electrode body 100 having the solid electrolyte 202 is immersed in the liquid electrolyte 203, and vacuum drawing is repeated multiple times to allow the liquid electrolyte 203 to be adsorbed onto the electrode body. The combination of the liquid electrolyte 203 and the solid electrolyte 202 is the hybrid electrolyte 200. After the wound blank electrode body 100 having the hybrid electrolyte 200 is placed in the case 301, the cap 302 is fitted onto the case 301, and then the gap between the case 301, the cap 302, the anode lead 104, and the cathode lead 105 is sealed with the sealant 303 to form the sealed body 300, that is, the hybrid electrolytic capacitor (including the solid electrolyte 202 and the liquid electrolyte 203) is formed.
[0024] 2A, the solid electrolytic capacitor includes an anode foil 101 (having a dielectric oxide film 201 thereon), a cathode foil 103, and a separator 102 located between the anode foil 101 and the cathode foil 103. A solid electrolyte 202 is formed on the surface of the dielectric oxide film 201 on the anode foil 101, and the solid electrolyte 202 includes a conductive polymer and a zwitterionic compound, the chemical structure of which is as follows:
[0025] [ka]
[0026] R 1 is C 1-6 R is a straight or branched alkyl group. 2 , R 3 , and R 4 are each independently H or C 1-6 is a straight or branched alkyl group of the formula 1-12 is a straight-chain or branched-chain alkylene group.
[0027] In some embodiments, the zwitterionic compound comprises 1 wt % to 50 wt % of the solid electrolyte 202. Too low a ratio of zwitterionic compound can have an effect similar to that of the absence of zwitterionic compound, while too high a ratio of zwitterionic compound can be detrimental to the properties of the conductive polymer matrix. In some embodiments, the conductive polymer includes poly(3,4-ethylenedioxythiophene:polystyrenesulfonate) (PEDOT:PSS), polythiophene, poly(p-phenylene sulfide), polycarbazole, polyindole, polyaniline, polypyrrole, poly(fluorene), polyphenylene, polypyrene, polyazulene, polynaphthalene, poly(acetylene), or poly(p-phenylene vinylene).
[0028] An embodiment of the present invention provides a hybrid electrolytic capacitor, as shown in FIG. 2B, which includes an anode foil 101 (having a dielectric oxide film 201 thereon), a cathode foil 103, and a separator 102 located between the anode foil 101 and the cathode foil 103. A solid electrolyte 202 is formed on the surface of the dielectric oxide film 201 on the anode foil 101, and the solid electrolyte 202 includes a conductive polymer. The type of the conductive polymer is as described above and will not be repeated here. A liquid electrolyte 203 is filled into the space between the anode foil, the cathode foil, and the separator. The liquid electrolyte 203 includes a solvent with a boiling point higher than 150° C.
[0029] In the hybrid electrolytic capacitor, the solid electrolyte 202, the liquid electrolyte 203, or both, include a zwitterionic compound, the chemical structure of which is as follows:
[0030] [ka]
[0031] R 1 is C 1-6 R is a straight or branched alkyl group. 2 , R 3 , and R 4 are each independently H or C 1-6 is a straight or branched alkyl group of the formula 1-12 is a straight-chain or branched-chain alkylene group.
[0032] In some embodiments, when the solid electrolyte 202 includes a zwitterionic compound, the zwitterionic compound comprises 1 wt% to 50 wt% of the solid electrolyte. If the ratio of the zwitterionic compound is too low, the effect is similar to that of the absence of the zwitterionic compound. If the ratio of the zwitterionic compound is too high, the properties of the conductive polymer matrix are adversely affected. In some embodiments, when the liquid electrolyte 203 includes a zwitterionic compound, the zwitterionic compound comprises 1 wt% to 50 wt% of the liquid electrolyte. If the ratio of the zwitterionic compound is too low, the effect is similar to that of the absence of the zwitterionic compound. If the ratio of the zwitterionic compound is too high, the viscosity increases and becomes too viscous, which is adverse to loading and adsorption. The optimal ratio is 10 wt% to 30 wt%.
[0033] In some embodiments, when solid electrolyte 202 and liquid electrolyte 203 include a zwitterionic compound, the chemical structure of the zwitterionic compound in solid electrolyte 202 and the chemical structure of the zwitterionic compound in liquid electrolyte 203 are the same.
[0034] In some embodiments, when solid electrolyte 202 and liquid electrolyte 203 include a zwitterionic compound, the chemical structure of the zwitterionic compound in solid electrolyte 202 and the chemical structure of the zwitterionic compound in liquid electrolyte 203 are different.
[0035] In some embodiments, the solvent with a boiling point higher than 150° C. includes propylene glycol, glycerol, gamma-butyrolactone, gamma-valerolactone, N-methylpyrrolidone, dimethyl sulfoxide, or sulfolane. If the boiling point of the solvent is lower than 150° C., it will expand and burst when heated to high temperatures, causing the electrolyte to leak and diffuse, and it is easy to cause a short circuit. For safety reasons, in some embodiments, the liquid electrolyte further includes a liquid polymer, such as a polyalkylene glycol. The liquid polymer helps to increase the stability of the liquid electrolyte. In some embodiments, the polyalkylene glycol may be a polyethylene glycol. In some embodiments, the molecular weight of the polyalkylene glycol may be 200 to 2000. If the molecular weight of the polyalkylene glycol is too low, the boiling point will be too low and will not meet the requirements. If the molecular weight of the polyalkylene glycol is too high, it may become a solid rather than a liquid.
[0036] It should be noted that the above-mentioned method of forming the capacitor is merely an example and is not intended to limit the present invention, and a person skilled in the art can form the capacitor according to the embodiment of the present invention using any method, including but not limited to the above-mentioned method.
[0037] The method for forming the zwitterionic compound may involve taking an imidazole compound and a sultone compound and reacting them, as follows: It should be understood that the methods for synthesizing the zwitterionic compound described below are merely illustrative and do not limit the present invention. A person having ordinary skill in the art can synthesize the zwitterionic compound using any method, not limited to the synthetic method described below.
[0038] [ka]
[0039] In some embodiments, the chemical structure of the zwitterionic compound formed by the above reaction may be any of those shown below, or any other suitable chemical structure.
[0040] [ka] [ka]
[0041] Experiments have shown that solid or hybrid electrolytic capacitors using zwitterionic compounds have lower low-temperature capacitance fade rates and lower low-temperature ESR increase rates.
[0042] In order to make the above-mentioned contents, as well as other objects, features and advantages of the present disclosure more clear and understandable, the present disclosure will be described in detail below with reference to the accompanying drawings. EXAMPLES
[0043] In the following examples, a wound blank electrode body (CHINSAN electronic) was used. The anode foil included in the wound blank electrode body is an aluminum foil whose surface is oxidized to a porous aluminum oxide (e.g., a dielectric oxide film), and the cathode foil is an aluminum foil whose surface is smooth, and a separator is interposed between the anode foil and the cathode foil. The anode foil, the cathode foil, and the separator were wound into a roll, and the anode lead and the cathode lead were connected to the anode foil and the cathode foil, respectively, to form a wound blank electrode body.
[0044] The wound blank electrode body was immersed in the dispersion liquid, and the vacuum was repeatedly pulled several times to allow the adsorption to proceed. The wound blank electrode body with the adsorbed dispersion liquid was then dried at high temperature for a certain period of time. The adsorption and drying steps were repeated three times, and a solid electrolyte was formed on the surface of the dielectric oxide film on the anode foil. The wound blank electrode body with the solid electrolyte was placed in a case. A cap was fitted onto the case, and then the gaps between the case, cap, anode lead, and cathode lead were sealed with a sealant to form a solid electrolytic capacitor (containing only solid electrolyte, no liquid electrolyte).
[0045] Also, after the solid electrolyte was formed on the surface of the porous aluminum oxide (e.g., a dielectric oxide film) on the anode foil, the wound blank electrode body with the solid electrolyte was immersed in the liquid electrolyte, and the vacuum was repeatedly drawn multiple times to ensure that the liquid electrolyte was well adsorbed on the electrode body. The combination of the liquid electrolyte and the solid electrolyte is the hybrid electrolyte. After the wound blank electrode body with the hybrid electrolyte was placed in a case, a cap was fitted onto the case, and then the gaps between the case, the cap, the anode lead, and the cathode lead were sealed with a sealant to form a hybrid electrolytic capacitor (containing a solid electrolyte and a liquid electrolyte).
[0046] In the following examples, the viscosity of the dispersion or liquid electrolyte was measured at a shear rate of 100 Hz and 25° C. using a rheometer (Brookfield LVDV-II pro).
[0047] In the following examples, the dispersion (2.5 g) was dried at 130° C. for 3 hours, and the solid content of the dispersion was measured by differential weighing.
[0048] In the following examples, an LCR meter (Agilent 4263B) was used to measure the capacitance of a capacitor at room temperature, -40°C, and -55°C at 35 V at 120 Hz, and the low-temperature capacitance decay rate (%) of the capacitor at low temperature compared to that of the capacitor at room temperature was calculated.
[0049] In the following examples, an LCR meter (Agilent 4263B) was used to measure the equivalent series resistance (ESR) of the capacitors at room temperature, -40°C, and -55°C at 35 V at 100 KHz, and the low-temperature ESR increase rate (%) of the capacitor at low temperature compared to the capacitor at room temperature was calculated.
[0050] Synthesis example 1 (compound I-1) 1-Methylimidazole (24.6g, 0.3mol) was dissolved in ethylene glycol dimethyl ether (100g) and heated to 80°C under nitrogen system. Within 1 hour, 1,4-butanesultone (40.8g, 0.3mol) was added dropwise into the solution, and then the solution was kept at 80°C for 3 hours of reaction, and then the temperature was lowered to 0°C to 5°C to precipitate a white solid. The solid was collected after filtration and dried under vacuum to obtain compound I-1 (43.2g). Its appearance was white crystals. The proton spectrum of compound I-1 was as follows: 1 H-NMR (500MHz, CD3OD): 1.78-1.84 (m, 2H), 2.04-2.10 (m, 2H), 2.87 (t, 2H, J = 7.5Hz), 3.96 (s, 3H), 4.29 (t, 2H, J = 7.3Hz), 7.59 (d, 1H, J = 2.5Hz), 7.68 (d, 1H, J = 2.5Hz), 8.99 (s, 1H). The carbon spectrum of compound I-1 was as follows. 13 C-NMR (125MHz, CD3OD): 22.88, 30.00, 36.69, 50.44, 51.61, 123.83, 125.13, 138.12. The above reaction is shown in the following formula.
[0051] [ka]
[0052] Synthesis example 2 (compound I-2) 1,2-Dimethylimidazole (28.8g, 0.3mol) was dissolved in ethylene glycol dimethyl ether (100g) and heated to 80°C under nitrogen system. Within 1 hour, 1,4-butanesultone (40.8g, 0.3mol) was added dropwise into the solution, and then the solution was kept at 80°C for 3 hours of reaction, and then the temperature was lowered to 0°C to 5°C to precipitate a white solid. The solid was collected after filtration and dried under vacuum to obtain compound I-2 (60.2g). Its appearance was white crystals. The proton spectrum of compound I-2 was as follows: 1 H-NMR (500MHz, CD3OD): 1.82-1.88 (m, 2H), 2.02-2.08 (m, 2H), 2.70 (s, 3H), 2.89 (t, 2H, J = 7.3Hz), 3.87 (s, 3H), 4.25 (t, 2H, J = 7.50Hz), 7.52 (d, 1H, J = 2.0Hz), 7.59 (d, 1H, J = 2.0Hz). The carbon spectrum of compound I-2 was as follows. 13 C-NMR (125MHz, CD3OD): 9.67, 22.99, 29.59, 35.54, 51.58, 122.38, 123.78, 146.12. The above reaction is shown in the following formula.
[0053] [ka]
[0054] Preparation example 1 (liquid electrolyte H-1) Propylene glycol (50 g) and compound I-1 (25 g) were mixed and then heated to dissolve, and then liquid polymer PEG-400 (25 g) was added. After stirring and cooling to room temperature, liquid electrolyte H-1 was obtained.
[0055] Preparation example 2 (liquid electrolyte H-2) Propylene glycol (85 g) and compound I-2 (15 g) were mixed and then heated to dissolve, stirred, and cooled to room temperature to obtain liquid electrolyte H-2.
[0056] Preparation example 3 (liquid electrolyte H-3) Propylene glycol (60 g) and liquid polymer PEG-400 (30 g) were mixed and then heated to dissolve. After stirring and cooling to room temperature, liquid electrolyte H-3 was obtained.
[0057] Preparation Example 4 (Dispersion D-1 containing no zwitterionic compound) A liquid containing 1.3% PEDOT / PSS (85 g, CP-WL2A purchased from Ohtsu Polymers, pH = 4.0) was taken and mixed with a mixed liquid (15 g, weight ratio of propylene glycol:glycerol:PEG-400 was 1:2:2) and stirred vigorously to homogenize, obtaining dispersion D-1.
[0058] Preparation Example 5 (Dispersion D-2 containing Compound I-1) A liquid containing 1.3% PEDOT / PSS (85 g, CP-WL2A purchased from Ohtsu Polymer, pH = 4.0) was taken and mixed with a mixture (14 g, weight ratio of propylene glycol:glycerol:PEG-400 was 1:2:2) and compound I-1 (1 g) by vigorously stirring to homogenize, to obtain dispersion D-2.
[0059] The properties of the above-mentioned liquid electrolyte and dispersion are shown in Table 1.
[0060] [Table 1]
[0061] Dispersions D-1 and D-2 were maintained at a pH of 3 to 4, a solid content of 9% to 10%, and a low viscosity (<15 cP). The viscosity of the liquid electrolyte was kept below 60 cP in both cases, which improved the adsorption conditions when the wound blank electrode body was immersed in the subsequent step.
[0062] Example 1 (Solid electrolytic capacitor) The wound blank electrode body was immersed in the dispersion liquid D-2, and the vacuum was repeated eight times to allow the adsorption to proceed. The wound blank electrode body with the dispersion liquid D-2 adsorbed thereon was then dried for 30 minutes at 135°C. The adsorption and drying steps were repeated three times to form a solid electrolyte on the surface of the porous aluminum oxide (e.g., dielectric oxide film) on the anode foil. The wound blank electrode body with the solid electrolyte was placed in a case. A cap was fitted onto the case, and then the gaps between the case, cap, anode lead, and cathode lead were sealed with a sealant to form a solid electrolytic capacitor. The capacitance and ESR of the capacitor at each temperature were measured, and the capacity decay rate and ESR increase rate at each temperature were calculated.
[0063] Example 2 (Hybrid electrolytic capacitor) The wound blank electrode body was immersed in the dispersion liquid D-1, and the vacuum was repeated eight times to allow the adsorption to proceed. The wound blank electrode body with the dispersion liquid D-1 adsorbed thereon was then dried for 30 minutes at 135°C. The adsorption and drying steps were repeated three times to form a solid electrolyte on the surface of the porous aluminum oxide (e.g., dielectric oxide film) on the anode foil. The wound blank electrode body with the solid electrolyte was immersed in the liquid electrolyte H-1, and the vacuum was repeated eight times to allow the liquid electrolyte H-1 to be well adsorbed on the electrode body. The combination of the liquid electrolyte H-1 and the solid electrolyte is the hybrid electrolyte. After the wound blank electrode body with the hybrid electrolyte was placed in the case, the cap was fitted on the case, and then the gaps between the case, the cap, the anode lead, and the cathode lead were sealed with a sealant to form a hybrid electrolytic capacitor. The capacitance and ESR of the capacitor at each temperature were measured, and the capacity decay rate and ESR increase rate at each temperature were calculated.
[0064] Example 3 (Hybrid electrolytic capacitor) The wound blank electrode body was immersed in the dispersion D-2, and the vacuum was repeated eight times to allow the adsorption to proceed. The wound blank electrode body with the dispersion D-2 adsorbed thereon was then dried for 30 minutes at 135°C. The adsorption and drying steps were repeated three times to form a solid electrolyte on the surface of the porous aluminum oxide (e.g., dielectric oxide film) on the anode foil. The wound blank electrode body with the solid electrolyte was immersed in the liquid electrolyte H-1, and the vacuum was repeated eight times to allow the liquid electrolyte H-1 to be well adsorbed on the electrode body. The combination of the liquid electrolyte H-1 and the solid electrolyte is the hybrid electrolyte. After the wound blank electrode body with the hybrid electrolyte was placed in the case, the cap was fitted on the case, and then the gaps between the case, the cap, the anode lead, and the cathode lead were sealed with a sealant to form a hybrid electrolytic capacitor. The capacitance and ESR of the capacitor at each temperature were measured, and the capacity decay rate and ESR increase rate at each temperature were calculated.
[0065] Example 4 (Hybrid electrolytic capacitor) The wound blank electrode body was immersed in the dispersion liquid D-1, and the vacuum was repeated eight times to allow the adsorption to proceed. The wound blank electrode body with the dispersion liquid D-1 adsorbed thereon was then dried for 30 minutes at 135°C. The adsorption and drying steps were repeated three times to form a solid electrolyte on the surface of the porous aluminum oxide (e.g., dielectric oxide film) on the anode foil. The wound blank electrode body with the solid electrolyte was immersed in the liquid electrolyte H-2, and the vacuum was repeated eight times to allow the liquid electrolyte H-2 to be well adsorbed on the electrode body. The combination of the liquid electrolyte H-2 and the solid electrolyte is the hybrid electrolyte. After the wound blank electrode body with the hybrid electrolyte was placed in the case, the cap was fitted on the case, and then the gaps between the case, the cap, the anode lead, and the cathode lead were sealed with a sealant to form a hybrid electrolytic capacitor. The capacitance and ESR of the capacitor at each temperature were measured, and the capacity decay rate and ESR increase rate at each temperature were calculated.
[0066] Example 5 (Hybrid electrolytic capacitor) The wound blank electrode body was immersed in the dispersion D-2, and the vacuum was repeated eight times to allow the adsorption to proceed. The wound blank electrode body with the dispersion D-2 adsorbed thereon was then dried for 30 minutes at 135°C. The adsorption and drying steps were repeated three times to form a solid electrolyte on the surface of the porous aluminum oxide (e.g., dielectric oxide film) on the anode foil. The wound blank electrode body with the solid electrolyte was immersed in the liquid electrolyte H-2, and the vacuum was repeated eight times to allow the liquid electrolyte H-2 to be well adsorbed on the electrode body. The combination of the liquid electrolyte H-2 and the solid electrolyte is the hybrid electrolyte. After the wound blank electrode body with the hybrid electrolyte was placed in the case, the cap was fitted on the case, and then the gaps between the case, the cap, the anode lead, and the cathode lead were sealed with a sealant to form a hybrid electrolytic capacitor. The capacitance and ESR of the capacitor at each temperature were measured, and the capacity decay rate and ESR increase rate at each temperature were calculated.
[0067] Example 6 (Hybrid electrolytic capacitor) The wound blank electrode body was immersed in the dispersion D-2, and the vacuum was repeated eight times to allow the adsorption to proceed. The wound blank electrode body with the dispersion D-2 adsorbed thereon was then dried for 30 minutes at 135°C. The adsorption and drying steps were repeated three times to form a solid electrolyte on the surface of the porous aluminum oxide (e.g., dielectric oxide film) on the anode foil. The wound blank electrode body with the solid electrolyte was immersed in the liquid electrolyte H-3, and the vacuum was repeated eight times to allow the liquid electrolyte H-3 to be well adsorbed on the electrode body. The combination of the liquid electrolyte H-3 and the solid electrolyte is the hybrid electrolyte. After the wound blank electrode body with the hybrid electrolyte was placed in the case, the cap was fitted on the case, and then the gaps between the case, the cap, the anode lead, and the cathode lead were sealed with a sealant to form a hybrid electrolytic capacitor. The capacitance and ESR of the capacitor at each temperature were measured, and the capacity decay rate and ESR increase rate at each temperature were calculated.
[0068] Comparative Example 1 (Solid Electrolytic Capacitor) The wound blank electrode body was immersed in the dispersion liquid D-1, and the vacuum was repeated eight times to allow the adsorption to proceed. The wound blank electrode body with the dispersion liquid D-1 adsorbed thereon was then dried for 30 minutes at 135°C. The adsorption and drying steps were repeated three times to form a solid electrolyte on the surface of the porous aluminum oxide (e.g., dielectric oxide film) on the anode foil. The wound blank electrode body with the solid electrolyte was placed in a case. A cap was fitted onto the case, and then the gaps between the case, cap, anode lead, and cathode lead were sealed with a sealant to form a solid electrolytic capacitor. The capacitance and ESR of the capacitor at each temperature were measured, and the capacity decay rate and ESR increase rate at each temperature were calculated.
[0069] Comparative Example 2 (Hybrid Electrolytic Capacitor) The wound blank electrode body was immersed in the dispersion liquid D-1, and the vacuum was repeated eight times to allow the adsorption to proceed. The wound blank electrode body with the dispersion liquid D-1 adsorbed thereon was then dried for 30 minutes at 135°C. The adsorption and drying steps were repeated three times to form a solid electrolyte on the surface of the porous aluminum oxide (e.g., dielectric oxide film) on the anode foil. The wound blank electrode body with the solid electrolyte was immersed in the liquid electrolyte H-3, and the vacuum was repeated eight times to allow the liquid electrolyte H-3 to be well adsorbed on the electrode body. The combination of the liquid electrolyte H-3 and the solid electrolyte is the hybrid electrolyte. After the wound blank electrode body with the hybrid electrolyte was placed in the case, the cap was fitted on the case, and then the gaps between the case, the cap, the anode lead, and the cathode lead were sealed with a sealant to form a hybrid electrolytic capacitor. The capacitance and ESR of the capacitor at each temperature were measured, and the capacity decay rate and ESR increase rate at each temperature were calculated.
[0070] The configuration of the above-mentioned capacitor and the capacity decay rate at each temperature (compared to the capacity at room temperature) are shown in Table 2.
[0071] [Table 2]
[0072] Table 2 shows Example 1 of a solid electrolyte containing compound I-1, and the low-temperature capacity fade rate (δCap) of the solid electrolytic capacitor is lower than that of Comparative Example 1, indicating that the zwitterionic compound, for example, compound I-1, can improve the problem of low-temperature capacity decline. The hybrid electrolytic capacitor of Comparative Example 2 has a good low-temperature capacity fade rate at -40°C (-13.6%), but a poor low-temperature capacity fade rate at severe low temperatures, for example, at -55°C (-20.8%). The hybrid electrolytic capacitors of Examples 2 to 6 of the present invention not only have a good low-temperature capacity fade rate at -40°C (best -11.8%), but also have a low-temperature capacity fade rate at more severe low temperatures, for example, at -55°C (best -16.2%) that are superior to Comparative Example 2. As can be seen from the above, the low-temperature capacity fade rate of the hybrid electrolytic capacitor can be suppressed by adding a zwitterionic compound (for example, compound I-1 or I-2) to the solid electrolyte, liquid electrolyte, or both.
[0073] [Table 3]
[0074] As shown in Table 3, the solid electrolytic capacitors or hybrid electrolytic capacitors using the zwitterionic compounds in the examples of the present invention all had lower ESR increase rates than the comparative examples at a harsh temperature of -55°C. The above experiments prove that the low-temperature ESR increase rate of the electrolytic capacitors using the zwitterionic compounds is lower.
[0075] Although the present disclosure has been disclosed above by some preferred embodiments, these are not intended to limit the present disclosure, and those skilled in the art can make any changes and modifications without departing from the spirit and scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on what is defined in the appended claims. [Explanation of symbols]
[0076] 100 ···Wound blank electrode body 101 Anode foil 102 Separator 103 Cathode foil 104 Anode lead 105 Cathode lead 200 Hybrid electrolyte 201...Dielectric oxide film 202...Solid electrolyte 203...liquid electrolyte 300...Sealing body 301...Case 302 Cap 303 Sealing material
Claims
1. A solid electrolytic capacitor comprising: an anode foil having a dielectric oxide coating thereon; A cathode foil; a separator located between the anode foil and the cathode foil; a solid electrolyte formed on the surface of the dielectric oxide film on the anode foil; Including, 1. A solid electrolytic capacitor, wherein the solid electrolyte comprises a conductive polymer and a zwitterionic compound, and the chemical structure of the zwitterionic compound is as follows: 【Chemistry 1】 (In the formula, R 1 is C 1-6 R is a straight or branched alkyl group of 2 , R 3 , and R 4 are each independently H or C 1-6 and L is a straight or branched alkyl group of C 1-12 is a straight-chain or branched-chain alkylene group.
2. 2. The solid electrolytic capacitor of claim 1, wherein the zwitterionic compound comprises 1 wt % to 50 wt % of the solid electrolyte.
3. 2. The solid electrolytic capacitor of claim 1, wherein the conductive polymer includes poly3,4-ethylenedioxythiophene:polystyrenesulfonate (PEDOT:PSS), polythiophene, poly(p-phenylene sulfide), polycarbazole, polyindole, polyaniline, polypyrrole, poly(fluorene), polyphenylene, polypyrene, polyazulene, polynaphthalene, poly(acetylene), or poly(p-phenylene vinylene).
4. 1. A hybrid electrolytic capacitor, comprising: an anode foil having a dielectric oxide coating thereon; A cathode foil; a separator located between the anode foil and the cathode foil; a solid electrolyte formed on the surface of the dielectric oxide film on the anode foil and including a conductive polymer; a liquid electrolyte filled in a space between the anode foil, the cathode foil, and the separator, the liquid electrolyte including a solvent having a boiling point higher than 150° C.; 1. A hybrid electrolytic capacitor, wherein the solid electrolyte, the liquid electrolyte, or both, comprise a zwitterionic compound, the chemical structure of which is: 【Chemistry 2】 (In the formula, R 1 is C 1-6 R is a straight or branched alkyl group of 2 , R 3 , and R 4 are each independently H or C 1-6 and L is a straight or branched alkyl group of C 1-12 is a straight-chain or branched-chain alkylene group.
5. 5. The hybrid electrolytic capacitor of claim 4, wherein when the solid electrolyte includes the zwitterionic compound, the zwitterionic compound comprises 1 wt % to 50 wt % of the solid electrolyte.
6. 5. The hybrid electrolytic capacitor of claim 4, wherein when the liquid electrolyte includes the zwitterionic compound, the zwitterionic compound comprises 1 wt % to 50 wt % of the liquid electrolyte.
7. 5. The hybrid electrolytic capacitor of claim 4, wherein when the solid electrolyte and the liquid electrolyte contain the zwitterionic compound, a chemical structure of the zwitterionic compound in the solid electrolyte and a chemical structure of the zwitterionic compound in the liquid electrolyte are the same.
8. 5. The hybrid electrolytic capacitor of claim 4, wherein when the solid electrolyte and the liquid electrolyte contain the zwitterionic compound, a chemical structure of the zwitterionic compound in the solid electrolyte is different from a chemical structure of the zwitterionic compound in the liquid electrolyte.
9. 5. The hybrid electrolytic capacitor of claim 4, wherein the solvent having a boiling point higher than 150° C. includes propylene glycol, glycerol, gamma-butyrolactone, gamma-valerolactone, N-methylpyrrolidone, dimethylsulfoxide, or sulfolane.
10. 5. The hybrid electrolytic capacitor of claim 4, wherein the liquid electrolyte further comprises a liquid polymer.
11. The hybrid electrolytic capacitor of claim 10 , wherein the liquid polymer comprises a polyalkylene glycol.